2010
DOI: 10.1371/journal.pone.0011633
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Supralittoral Rocky Intertidal Ligia Isopods in the Pacific Region from Central California to Central Mexico

Abstract: Background Ligia isopods are widely distributed in the Pacific rocky intertidal shores from central California to central Mexico, including the Gulf of California. Yet, their biological characteristics restrict them to complete their life cycles in a very narrow range of the rocky intertidal supralittoral. Herein, we examine phylogeographic patterns of Ligia isopods from 122 localities between central California and central Mexico. We expect to find high levels of allopatric diversity. In addition, we expect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
201
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 84 publications
(216 citation statements)
references
References 47 publications
13
201
2
Order By: Relevance
“…However, several semiterrestrial coastal species do not show clear relationships between their distributions and local ocean currents (e.g., coastal tiger beetles: Satoh et al, 2004, Ligia spp. : Itani, 2000Hurtado et al, 2010).…”
Section: Distribution Patterns Of Populations and Their Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several semiterrestrial coastal species do not show clear relationships between their distributions and local ocean currents (e.g., coastal tiger beetles: Satoh et al, 2004, Ligia spp. : Itani, 2000Hurtado et al, 2010).…”
Section: Distribution Patterns Of Populations and Their Relationshipsmentioning
confidence: 99%
“…Phylogenetic analyses of mitochondrial DNA data have revealed that some semiterrestrial coastal isopods display noncurrent-related and complex distribution patterns in several areas (Ligia spp. : Itani, 2000;Hurtado et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…First, they are widely distributed along the coast of the Gulf of California, its islands, and the Pacific coast of the Baja California peninsula. Hurtado et al (2010) report the presence of these isopods in 4100 coastal localities in this region, which are subject to varying levels of anthropogenic activity, and they are likely to be found at many yet unexplored localities. Second, they occur exclusively at beaches with rocky supralittoral zones, where they are restricted to the narrow range between the splash zone and the supralittoral.…”
Section: Introductionmentioning
confidence: 99%
“…The wharf roach (Ligia sp., Crustacea, Isopoda, Ligiidae) is a cosmopolitan semi-terrestrial crustacean distributed in temperate and tropical areas [8][9][10]. Abundant wharf roaches can be found on the seashore among pilings, beach fortifications, jetties, and rocks in most estuary and coastal areas of Japan [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Abundant wharf roaches can be found on the seashore among pilings, beach fortifications, jetties, and rocks in most estuary and coastal areas of Japan [11,12]. Owing to some of their ecophysiological characteristics, these crustaceans are highly constrained throughout their life cycle to remain on the same beach [10], and thus may serve as a good bioindicator of radioactive contamination of their habitats [13].…”
Section: Introductionmentioning
confidence: 99%